Single cell transcriptomic analysis of the canine duodenum in chronic inflammatory enteropathy and health - Manchester, Alison C.; Ammons, Dylan T.; Lappin, Michael R.; Dow, Steven (Frontiers in Immunology, 2024)
Chronic inflammatory enteropathy (CIE) is a common condition in dogs causing recurrent or persistent gastrointestinal clinical signs. Pathogenesis is thought to involve intestinal mucosal inflammatory infiltrates, but histopathological evaluation of intestinal biopsies from dogs with CIE fails to guide treatment, inform prognosis, or correlate with clinical remission. We employed single-cell RNA sequencing to catalog and compare the diversity of cells present in duodenal mucosal endoscopic biopsies from 3 healthy dogs and 4 dogs with CIE. Through characterization of 35,668 cells, we identified 31 transcriptomically distinct cell populations, including T cells, epithelial cells, and myeloid cells. Both healthy and CIE samples contributed to each cell population. T cells were broadly subdivided into GZMAhigh (putatively annotated as tissue resident) and IL7Rhigh (putatively annotated as non-resident) T cell categories, with evidence of a skewed proportion favoring an increase in the relative proportion of IL7Rhigh T cells in CIE dogs. Among the myeloid cells, neutrophils from CIE samples exhibited inflammatory (SOD2 and IL1) gene expression signatures. Numerous differentially expressed genes were identified in epithelial cells, with gene set enrichment analysis suggesting enterocytes from CIE dogs may be undergoing stress responses and alter their metabolic properties. Overall, this work reveals the previously unappreciated cellular heterogeneity in canine duodenal mucosa and provides new insights into molecular mechanisms which may contribute to intestinal dysfunction in CIE. The cell type gene signatures developed through this study may also be used to better understand the subtleties of canine intestinal physiology in health and disease.